2003
DOI: 10.1046/j.1365-313x.2003.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation tagging, a novel tool to dissect the functions of a gene family

Abstract: SummaryIn a screen for morphological mutants from the T 1 generation of approximately 50 000 activation-tagging lines, we isolated four dominant mutants that showed hyponastic leaves, downward-pointing¯owers and decreased apical dominance. We designated them isoginchaku (iso). The iso-1D and iso-2D are allelic mutants caused by activation of the AS2 gene. The T-DNAs were inserted in the 3 H downstream region of AS2. Iso-3D and iso-4D are the other allelic mutants caused by activation of the ASL1/LBD36 gene. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 19 publications
4
137
0
5
Order By: Relevance
“…Five of the 24 recovered LBD20-OX plants appeared similar to the wild type, nine were sterile, and five died. Similar phenotypes have been observed in plants overexpressing some other LBD genes (Shuai et al, 2002;Nakazawa et al, 2003;Naito et al, 2007). LBD20-OX transformants with milder phenotypes set viable seed and were used in subsequent experiments.…”
Section: And Pathogenesis Related4supporting
confidence: 55%
See 1 more Smart Citation
“…Five of the 24 recovered LBD20-OX plants appeared similar to the wild type, nine were sterile, and five died. Similar phenotypes have been observed in plants overexpressing some other LBD genes (Shuai et al, 2002;Nakazawa et al, 2003;Naito et al, 2007). LBD20-OX transformants with milder phenotypes set viable seed and were used in subsequent experiments.…”
Section: And Pathogenesis Related4supporting
confidence: 55%
“…While knockout mutations of most LBD genes show no obvious phenotypes, their overexpression in many cases results in leaf phenotypes like lobed and curled leaves, along with dwarfing and degrees of infertility (Shuai et al, 2002;Nakazawa et al, 2003;Naito et al, 2007;Mangeon et al, 2011). Similarly, we observed no obvious morphological changes in leaf or root morphology in either lbd20 mutant, however both lines exhibited increased resistance to F. oxysporum accompanied by increased expression of a subset of JA-regulated defense genes.…”
Section: Discussionmentioning
confidence: 53%
“…Possible candidates include LBD genes that are closely related to AS2, such as LBD36/ASL1. Overexpression of ASL1 produces a phenotype that is similar to that of as2-5D, suggesting that AS2 and ASL1 have overlapping functions (25,26). If AS2 and ASL1 contribute redundantly to the kan1 kan2 phenotype, loss-of-function mutations in only one of these mutations may have little or no effect on this phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Based on its expression pattern, it has been postulated that LOB plays a role in the establishment of boundaries between the meristem and the differentiated lateral organs (Shuai et al, 2002). Other members of this AS2/LOB family have only been characterised by gain-of-function mutation (Nakazawa et al, 2003), which revealed remarkably similar phenotypes.…”
Section: Introductionmentioning
confidence: 99%